Rediscovering ‘Sacred Place’ through the Indigenous Religion Paradigm: A Case Study of Bugis-Makassar Indigenous People - Andi Alfian (Institut Agama Islam Negeri Kendari, 2022)
The Bugis-Makassar indigenous people who live around Mount Bawakaraeng perform a ritual pilgrimage (hajj) to the top of Mount Bawakaraeng (as a sacred space). This ritual is often considered heretical and deviant. These negative assumptions are the result of the monopoly definition of “sacred place” by the world religion paradigm which is only limited to the doctrine of the holy book and is hierarchical-exclusive. Meanwhile, in the indigenous religion paradigm, “sacred place” is closely related tothe surrounding environment (nature) which also gives life to indigenous peoples. The Bugis-Makassar indigenous people who live around Mount Bawakaraeng construct the sacredness of the mountain, not only as a place for religious rituals but also as a guarantor of their life. There were lacking previous researches discussing “sacred place” through the indigenous religion paradigm approach. This research contributes to that lack. This study examines how the indigenous religion paradigm interprets “sacred place”. The research method used in this research is qualitative. This study argues that there is no better way to understand why indigenous people perform rituals on Mount Bawakaraeng than using the indigenous religion paradigm. This study also shows that the “sacred place” associated with Mount Bawakaraeng is a way for the indigenous people who live around the mountain to preserve the nature around them which has enabled them to live and make a living such as accessing water, gathering medicines from nature, and so on. Eventually, with research that provides a better explanation of what a “sacred place” is in the indigenous religion paradigm, negative assumptions about indigenous people who regard a mountain as sacredplace can be better understood.